Evaluation of maize hybrids in Terai and inner Terai ecological belt of Nepal - Koirala, K. B.; Rijal, T. R.; KC, G.; Khan, S.; Mahato, D. N.; Manandhar, S.; Subedi, S.; Tripathi, M. P. (Journal of Agriculture and Forestry University, 2020)
Hybrid is the most economical option to boost up the grain yield of maize, and slowly it is gaining popularity among the farmers of Nepal. In order to identify the potential hybrids suitable for Terai and Inner Terai regions, a set of experiment was conducted on hybrid maize developed by National Maize Research Program (NMRP), Rampur in Coordinated Variety Trials (CVTs) during the winter season of 2014/15 and 2015/16. The experiments were done by using Randomized Complete Block Design (RCBD). Each treatment was replicated thrice for each site at Rampur, Belachapi, Tarahara, and Parwanipur. Over the years, genotypes RML-83/RL-197 and RML-4/RL-111 yielded higher than other tested genotypes in Tarahara. Similarly, RL-180/RL-105, RML-87/RL-105, Dekalb double and Rampur Hybrid-6 produced higher grain yield at Belachapi during 2014/15. Genotype RML-4/RML-111 followed by RML-98/RL-105, and Rampur Hybrid-6 yielded higher at Parwanipur during 2015/16. In the case of Rampur, genotypes RML-98/RML-105 had produced higher yield in both the years whereas RML-5/RL-105 during 2014/15, and Rampur Hybrid-2 followed by RML-55/RL-105 were the superior genotypes in terms of grain yield during 2015/16. Those hybrids with higher grain yield in CVTs will be upgraded to Coordinated Farmers Field Trial on Hybrid (CFFTH) and these hybrids might be the potential future hybrids for Terai and Inner Terai of Nepal.